18x+25=24x+13

Simple and best practice solution for 18x+25=24x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18x+25=24x+13 equation:



18x+25=24x+13
We move all terms to the left:
18x+25-(24x+13)=0
We get rid of parentheses
18x-24x-13+25=0
We add all the numbers together, and all the variables
-6x+12=0
We move all terms containing x to the left, all other terms to the right
-6x=-12
x=-12/-6
x=+2

See similar equations:

| 60+132d-36=-d+7 | | X=525-(63-5x) | | 4t+2+5t-8t=0 | | (5x+9)=(3x+5) | | 0=-16x^2+36x-20 | | 4x^2-16x^2+16=0 | | (5x+10)=(8x-14) | | 5(n+6)+20=20 | | 5y+7=4y+10 | | (5x+9)(3x+5)=0 | | x/8=0.3 | | 165=58-y | | 5x+65=95 | | 9x-13=4x-2 | | 23b^2+85b+26=-4-2b^2 | | 3.26c=8 | | 3g=6+4g | | 20+312n=30+234n | | 5(20=p)=2(30+p) | | 15x-21=3(5x-7) | | 3/7c+4=1/7c-6 | | x/8=4.5=12 | | 19c+31=26c-24 | | 12.3=4.41x | | 77x-49=7 | | 6x-(5×+8)=-3 | | 25+6n=18+7.50n | | 7-2(5x+3)=9-10x | | 9x=^2 | | 15x^2-10=14x+3x^2 | | 5/3x+1/3x=7+7/3x | | 9x=x2 |

Equations solver categories